REVITALIZATION OF TRANSFORMATIONAL LEADERSHIP AND ITS ROLE IN IMPROVING SCHOOL QUALITY IN THE ERA OF DIGITALIZATION - Kinanti, Garlinda; Citriadin, Yudin; Badrun, Badrun (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
School principals have an important role in improving school quality in this era of digitalization. The principal's transformational leadership can have an impact on teacher competency and improve school quality. This research aims to understand transformational leadership and how to improve school quality. This research was carried out at SD Negeri Joho. The method used by researchers is a qualitative method. Data collection techniques were carried out using interviews and documentation. The research subject was the principal of SD Negeri Joho. The results of the research are 1) Revitalization of transformational leadership that transformational leadership is more focused on providing motivational support, respect, inspiration, collaboration and guiding towards organizational success. 2) The role of transformational leadership in improving school quality by: a) the principal as a manager, b) the principal as an inspirer, c) the principal as a motivator.